Mitogen Activated Protein Kinases - Jose Lozano (Frontiers Research Topics, 2017)
Mitogen-activated protein kinase (MAPK) pathways are evolutionarily conserved in all eukaryotes and allow cells to respond to changes in the physical and chemical properties of the environment and to produce an appropriate response by altering many cellular functions. MAPKs are among the most intensively studied signal transduction systems. MAPK research is a very dynamic field in which new perspectives are continuously opening to the scientific community. Importantly, many MAPK inhibitors have been developed during the last years and are currently being tested in preclinical and clinical assays for inflammatory diseases and cancer treatment. In this research topic, we have gathered 14 papers covering recent advances in different aspects of the MAPK research area that have provided valuable insight into the spatiotemporal dynamics, the regulation and functions of MAPK pathways, as well as their therapeutic potential. We hope that this Research Topic helps readers to have a better understanding of the progresses that have been made recently in the field of MAPK signalling. A deeper understanding of the these pathways will facilitate the development of innovative therapeutic approaches.